Thelon : a river sanctuary - Pelly, David F., 1948- (Canadian Recreational Canoeing Association, 1996)
David Pelly tells the Thelon's story, exploring the mystery of Man's relationship with this special place in the heart of Canada's vast Arctic barrenlands. From Thanadelthur and Telaruk to J.W. Tyrrell, John Hornby and Eric Morse, the history is detailed, complete and exciting. The Thelon is the setting for a compelling Canadian adventure tale -- with all its drama, intrigue, joy and tragedy. But the writer goes beyond that to contemplate the significance of the Thelon wilderness, and to examine its uncertain future."It is the richness of human experience, layered on top of the natural splendor